2020
DOI: 10.1177/2150132720959936
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes from a 1-Year, Real-World, Head-to-Head Comparison of OnabotulinumtoxinA and Topiramate for Headache Prevention in Adults With Chronic Migraine

Abstract: Introduction/Objective: Chronic migraine (CM) is associated with impaired health-related quality of life and substantial socioeconomic burden, but many people with CM are underdiagnosed and do not receive appropriate preventive treatment. OnabotulinumtoxinA and topiramate have demonstrated efficacy (treatment benefit under ideal conditions) for the prevention of headaches in people with CM in clinical trials, but real-world studies suggest markedly different clinical effectiveness (treatment benefit based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…Furthermore, BoNTA demonstrated its efficacy in about 70% of treated patients after three courses of BoNTA on all clinical and quality of life measures and a favorable benefit‐risk ratio in subsequent PREEMPT pooled subgroup analysis of CM patients with or without MOH 13–15 . Real‐world data have also been consistent with the positive benefit‐risk profile of BoNTA ascertained in all PREEMPT‐based publications, in addition to demonstrating improvements on patient‐reported outcomes (PROs), 16 even in the context of direct head‐to‐head comparison with topiramate 17 . Finally, real‐world long‐term experience with BoNTA in CM patients for up to four years of treatment supports its sustained efficacy and adequate safety and tolerability over time 18–20 …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, BoNTA demonstrated its efficacy in about 70% of treated patients after three courses of BoNTA on all clinical and quality of life measures and a favorable benefit‐risk ratio in subsequent PREEMPT pooled subgroup analysis of CM patients with or without MOH 13–15 . Real‐world data have also been consistent with the positive benefit‐risk profile of BoNTA ascertained in all PREEMPT‐based publications, in addition to demonstrating improvements on patient‐reported outcomes (PROs), 16 even in the context of direct head‐to‐head comparison with topiramate 17 . Finally, real‐world long‐term experience with BoNTA in CM patients for up to four years of treatment supports its sustained efficacy and adequate safety and tolerability over time 18–20 …”
Section: Introductionsupporting
confidence: 56%
“…[13][14][15] Real-world data have also been consistent with the positive benefit-risk profile of BoNTA ascertained in all PREEMPT-based publications, in addition to demonstrating improvements on patientreported outcomes (PROs), 16 even in the context of direct head-tohead comparison with topiramate. 17 Finally, real-world long-term experience with BoNTA in CM patients for up to four years of treatment supports its sustained efficacy and adequate safety and tolerability over time. [18][19][20] We have previously reported that a total of 65/81 (80.2%) patients were classified as either 50% or 75% responders after receiving 3 treatment cycles of 155 U-195 U BoNTA with a corresponding significant improvement in all clinical efficacy measures, including reduction of mean headache days/month, days with peak headache intensity >4/10, as well as intake of acute headache medications per month, compared with baseline.…”
Section: Introductionmentioning
confidence: 86%
“…Several real-world studies have been published, with findings consistent with PREEMPT studies in CM patients with and without MOH [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. Real-world studies primarily exploring the effectiveness and safety of BT-A compared to the baseline are summarized in Table 2 .…”
Section: Clinical Use Of Bt-a In the Treatment Of Chronic Migrainementioning
confidence: 56%
“…Well-controlled clinical trials have shown that patients with overuse of headache medication can be treated successfully with onabotulinumtoxinA and topiramate [45]. Comparative studies have shown that onabotulinumtoxinA is an effective and safe alternative for the treatment of chronic migraine in patients who discontinue topiramate treatment and can be started during the tapering of topiramate [46,47]. It should be noted however that combining classic migraine therapy with onabotulinum-toxinA injection should be avoided in order to allow a better understanding of the efficacy of each treatment in the individual patient.…”
Section: Onabotulinumtoxina and Chronic Migrainementioning
confidence: 99%